Penegakan Hukum Terhadap Peraturan Daerah Kota Sukabumi Nomor 2 Tahun 2021 Perubahan Atas Peraturan Daerah Nomor 17 Tahun 2011 Tentang Pengelolaan Sampah - Efendi, Rivan Dwi; Wijaya, Agus Rasyid Chandra (Verdict: Journal of Law Science, 2024)
This research is motivated by the importance of law enforcement against Regional Regulations in waste management related to wise structuring and supervision by considering development and development in Sukabumi City. The government of Sukabumi has established and enforced Sukabumi City Regional Regulation Number 2 of 2021 Amendments to Regional Regulation Number 17 of 2011 concerning Waste Management, in order to create a comfortable, clean and beautiful Sukabumi City. The main problems in this research are how the role of Law Enforcement and what obstacles are faced by the Office in Law Enforcement efforts against Sukabumi City Regional Regulation Number 2 of 2021 amendments to Regional Regulation Number 17 of 2011 concerning Waste Management. The research method used is a qualitative method with the type of empirical juridical research, namely research that combines normative legal provisions on every legal event that occurs in society or in other words combines secondary data in the form of regulations, laws and books, and primary data, namely data obtained from the field directly based on real events. The research uses the theory of Law Enforcement and Legal Certainty Theory. The results of the study explain that the role of law enforcers in carrying out their duties is still not optimal so that it is very difficult to overcome the problem of waste and the obstacles that exist in overcoming the problem of waste are the absence of socialization related to the sanctions for littering, the lack of cleaning personnel, and low human resources.